Criminal Careers and Drug Abuse Among Adolescents in Indonesia - Latif, Syahrul Akmal; Som, Ahmad Puad Mat; Novarizal, Riky (Universitas Islam Negeri Raden Fatah Palembang, 2024)
The engagement of adolescents in drug abuse cases is a complex process that requires explanation and reflection. This study aims to explain the criminal careers of adolescents engaged in drug abuse. Such inclinations are often overlooked in studies concerning adolescent involvement in drug abuse cases in Indonesia. In addition to addressing the inadequacies of prior research, this study aims to expound the criminal careers of adolescents involved in drug abuse cases in Indonesia. This is a descriptive qualitative study that utilizes primary and secondary data. The study's findings highlight three important situations of adolescents' criminal careers in drug abuse cases. Firstly, the initial phase of adolescent drug abuse is precipitated by experimentation, peer influence, and a curiosity about drugs. Secondly, active drug abuse among adolescents manifests in various forms such as users, abusers, and addicts. Lastly, active participation in drug abuse among adolescents leads to a progression in behavior from from users to dealers, users to sellers, and addicts to dealers. This study also emphasizes the need to explain the perceptions and motivations of adolescents who engage in drug abuse cases to acquire a better understanding of their conduct.